Student Teachersâ Perceptions of English Lecturersâ Competences - Rokhyati, Umi (Ahmad Dahlan Journal of English Studies, 2015)
AbstractIt is important to know the competence of lecturers because competent lecturers are needed to produce competent graduates. Students are good informant to know the lecturersâ competence because they intensively interact in the classroom. This research is to know the studentsâ perception of the lecturersâ competence focusing on the level of competence and the strengths and weaknesses of the competence. The result shows that students perceived positively on the pedagogical, personal, and professional competence of the lecturers.